2014
DOI: 10.11138/gchir/2014.35.1.027
|View full text |Cite
|
Sign up to set email alerts
|

Is ionized calcium a reliable predictor of hypocalcemia after total thyroidectomy? A before and after study

Abstract: Hypocalcemia may be the only complication precluding a short postoperative hospital stay after total thyroidectomy (1, 2). Much has been written in the literature about the possibility of identifying (using different methods and predictors) which thyroidectomy patients will develop symptomatic hypocalcemia and which will not. Some authors (3-6) consider early postoperative (24-hour) serum calcium levels and intraoperative identification of parathyroid glands to be important predictive factors. Others (7-9) hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…Like 'operative time', this variable affects the overall costs of the procedure, although this is due not so much to the method used as to the possible onset of postoperative hypocalcaemia, which can arise even as long as 48–72 h after the surgery, especially in hyperfunctioning goitres. In addition, the length of hospital stay varies according to local practices: the US authors, generally accustomed to short stays, habitually discharged their patients 24 h after TOETVA or MIVAT, whereas in the Asian and European studies hospital stays were prolonged beyond the 2 nd day, probably to monitor the levels of post-operative calcaemia;[ 40 41 42 43 44 45 46 47 48 49 50 51 52 ] this is indeed in line with our practice.…”
Section: Discussionsupporting
confidence: 69%
“…Like 'operative time', this variable affects the overall costs of the procedure, although this is due not so much to the method used as to the possible onset of postoperative hypocalcaemia, which can arise even as long as 48–72 h after the surgery, especially in hyperfunctioning goitres. In addition, the length of hospital stay varies according to local practices: the US authors, generally accustomed to short stays, habitually discharged their patients 24 h after TOETVA or MIVAT, whereas in the Asian and European studies hospital stays were prolonged beyond the 2 nd day, probably to monitor the levels of post-operative calcaemia;[ 40 41 42 43 44 45 46 47 48 49 50 51 52 ] this is indeed in line with our practice.…”
Section: Discussionsupporting
confidence: 69%
“…Two other studies have demonstrated that there is an increased risk of developing permanent hypocalcemia if the level of Ca in the blood remains at 2 mmol/L or less, 1–3 weeks after surgery [ 32 , 33 ]. Tartaglia et al revealed that measurement of iCa was more reliable than measurement of Ca in post-TT patients, in the immediate and long-term follow-up [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative temporary hypocalcemia is the most common complication after total thyroidectomy . In most studies, the rate of postoperative hypocalcemia ranges from 6% to 55% . Its incidence has been considered an indicator of the quality of the surgical procedure in the performance of total thyroidectomy.…”
Section: Introductionmentioning
confidence: 99%
“…1 In most studies, the rate of postoperative hypocalcemia ranges from 6% to 55%. [2][3][4][5] Its incidence has been considered an indicator of the quality of the surgical procedure in the performance of total thyroidectomy. The frequency of postoperative hypocalcemia depends on many factors related to the patient such as preoperative levels of vitamin D, the indication for surgery (cancer or benign condition), the size of the gland, the need for associated neck dissection and the experience of the surgeon.…”
Section: Introductionmentioning
confidence: 99%